Humanising gaming? The politics of posthuman agency in autobiographical videogames. (April 2022) - Gallagher, Rob
For many commentators autobiographical videogames represent a step towards a more human vision of digital play, promising to transform a medium still widely associated with mindless and dehumanising virtual violence into a vector for self-expression, empathy and understanding. Viewed through the lens of life-writing theory, however, the situation looks somewhat different. As scholars in this field have shown, works of auto/biography and life-writing have been instrumental in propagating ideas about agency, politics and the human that remain both pervasive and pernicious. Their work suggests that if we are to talk about 'humanising' videogames we must first address how understandings of the human are constituted and who they have historically excluded. Here developments in life-writing theory align with recent scholarship on how videogames undercut the liberal humanist conception of the autonomous agential subject by implicating players in complex assemblages of human and non-human actors. This work holds out another way of reading the encounter between gaming and auto/biography: as a catalyst for new forms of posthumanist life-writing, in which the autobiographical mode co-exists with what this article dubs the ludobiographical mode. If games are auto biographical to the extent that they involve creators giving an account of episodes from their own life, they are ludo biographical to the extent that they foreground the challenges videogames pose to humanism's vision of autonomous individuals in possession of their own bodies, stories and identities. This idea is elaborated through an analysis of That Dragon, Cancer (Numinous Games, 2016 ). Created by Ryan and Amy Green, the game documents the death of their developmentally disabled son Joel and their consequent crisis of faith. Controversial and widely discussed, it constitutes a rich case study in how autobiographical videogames raise irreducibly political questions about agency, identity and the (post)human.